Intake of sodium and potassium, sodium-potassium intake ratio, and their relation to the risk of diabetes mellitus - Sung Keun Park; Chang-Mo Oh; Jae-Hong Ryoo; Ju Young Jung (Scientific Reports)
Abstract We aimed to examine the effects of sodium and potassium intake on the risk of diabetes mellitus (DM). In a cohort of 99,552 working-age Korean adults (60,591 men; mean age 39.7 ± 6.9 and 38,961 women; mean age 38.4 ± 6.5), we longitudinally evaluated the risk of DM in relation to quartile levels of sodium intake, potassium intake, and the sodium-potassium ratio. A Cox proportional hazards model was used to assess the risk of DM by calculating adjusted hazard ratios (HRs) and 95% confidence intervals (CIs) for incident DM (adjusted HR [95% CI]). In men, sodium intake was not associated with the risk of DM (first quartile: reference, second quartile: 0.96 [0.87–1.07], third quartile: 0.94 [0.84–1.05], and fourth quartile: 1.02 [0.89–1.18]). Women did not show a significant association between sodium intake and the risk of DM (first quartile: reference, second quartile: 0.87 [0.69–1.09], third quartile: 1.02 [0.81–1.29], and fourth quartile: 1.01 [0.76–1.33]). Additionally, potassium intake and the sodium-potassium ratio were not significantly associated with the risk of DM in either men or women. In conclusion, no significant association was observed between sodium or potassium intake and the risk of DM among working-age Korean adults.